Pengembangan Lembar Kerja Peserta Didik Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Penalaran Matematika - Mahendra, As'ari Eka; Caswita, Caswita; Bharata, Haninda (Universitas Islam Negeri Raden Intan Lampung, 2019)
This development research aims to develop a problem based learning based worksheet to improve students' mathematical reasoning abilities. This study begins with a preliminary study (needs analysis), preparation of student worksheets, validation of student worksheets, initial field trials, and field tests. The subjects of this study were students of class XI MIA2 MA Ma'arif NU 05 Sekampung Lampung Timur. The results of the preliminary study indicate the need to develop problem based learning based worksheets. Preparation of student worksheets begins with drawing up a design and all its components based on the drafting guide. The results of the validation show that LKPD has met the standards of eligibility for content and design. The results of the initial field trials indicate that the student worksheet is included in the good category. The results of field tests show that students' mathematical reasoning aspects are quite good because more than 75% of students have fulfilled the minimum completeness criteria.